1996
DOI: 10.1021/np960001y
|View full text |Cite
|
Sign up to set email alerts
|

Briareins C−L, 10 New Briarane Diterpenoids from the Common Caribbean Gorgonian Briareum asbestinum

Abstract: Ten new diterpenoid representatives from the briarane skeletal class have been isolated from shallow water colonies of the Caribbean gorgonian octocoral Briareum asbestinum collected at Mona Island near Puerto Rico. The structures of the new secondary metabolites, named briareins C−L (3−12), were defined by chemical and spectroscopic methods. In addition, two known diterpenoids, briareins A (1) and B (2), were among the most abundant compounds isolated. Traces of another known diterpenoid, briarane methyl este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Its 13 C and 1 H NMR data (Tables 1 and 2) were similar to those of 11 with the difference of some additional signals for an acetate ester, an isovalerate ester, and an oxymethyl (d C 53.0, q). In 4, the 1 H and 13 C NMR spectra showed the existence of four acetate and one isovalerate groups which were assigned to C-2, C-9, C-12, C-14, and C-13 because their carbonyl carbons were correlated with the corresponding oxymethine protons in the HMBC spectrum.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…Its 13 C and 1 H NMR data (Tables 1 and 2) were similar to those of 11 with the difference of some additional signals for an acetate ester, an isovalerate ester, and an oxymethyl (d C 53.0, q). In 4, the 1 H and 13 C NMR spectra showed the existence of four acetate and one isovalerate groups which were assigned to C-2, C-9, C-12, C-14, and C-13 because their carbonyl carbons were correlated with the corresponding oxymethine protons in the HMBC spectrum.…”
Section: Resultsmentioning
confidence: 58%
“…Its 13 C and 1 H NMR data (Tables 1 and 3) were closely similar to those of 11 with the only difference of an additional acetate group attached to the oxymethylene C-16 because of the HMBC correlations of d H 4.75, 5.04 (each d, J¼15.6 Hz, H-16) and 2.12 (3H, s) with d C 170.5 (s). Based on complete NMR study, the structure of juncin W (6) was inferred as shown in Figure 1, and its relative stereochemistry was proved to be the same as that of 1.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…1,2) The majority of these compounds are endowed with biological activities that ranges from cytotoxic [3][4][5] to anti-inflammatory, 6,7) immunomodulatory, 8) antiviral, 9) and insecticidal 10,11) actions. In continuation of our interest in the chemistry and potential medicinal importance of briaranes, [12][13][14] we investigated the gorgonian octocoral Junceella juncea collected in Taiwan.…”
mentioning
confidence: 99%